Behavioral Factors Against Hepatitis A Incidence in Universitas Jember with Lawrence Green Method - Eva Sulawati Arum; Sri Hernawati; Erma Sulistyaningsih (Humanistic Network for Science and Technology (HNST), 2021)
Hepatitis A is an inflammatory liver disease caused by Hepatitis A virus is Ribonucleic Acid (RNA) Virus. Hepatitis A viruses belonging to the family picornaviridae, genus hepatovirus, have 1 serotype and 4 genotypes. Outbreak of hepatitis A in the last 4 years, often occurs among students, especially students of the Universitas Jember. The results of observations made by researchers in September 2020, namely the level of knowledge of students of Universitas Jember was still less and could be more at risk of contracting hepatitis A compared to students who were well knowledgeable. The results of the data analysis showed that the level of knowledge of Universitas Jember students about hepatitis A could be more at risk of contracting hepatitis A compared to students who were well-knowledgeable. Knowledge of hepatitis A will certainly support the change in health behaviors, namely behaviors related to preventive, curative and rehabilitative efforts against hepatitis A. In general, students' knowledge of hepatits A was still half of respondents lack good knowledge of hepatitis A. Supportive behaviors in improving health are needed means to disseminate information about hepatitis A which includes preventive, curative and rehabilitative efforts. A person's knowledge of the disease is very important for the formation of actions that will be carried out by the person, because with good knowledge can create good actions. Keywords: behavior; hepatitis A; student